PEMODELAN TEMPERATUR DARI PROSES PEMBAKARAN DI REFORMER FURNACE PADA INDUSTRI BAJA - Trisaksono Bagus Priambodo (Badan Pengkajian dan Penerapan Teknologi, 2020)
Conversion processes that involve large amounts of energy include processes in furnace reformers inthe steel industry. The reformer unit used to convert the process gas, namely a mixture of gas andsteam into CO and H2 gas with the help of a nickel catalyst. The heat energy used in the process is theresult of combustion from natural gas using combustion located above the furnace. The most importantthing in the conversion process is the radiative heat transfer in the combustion chamber to the reactionpipe wall so that enough energy is obtained to carry out the conversion process. One way to determinethe heat distribution of the reformer combustion chamber is to know the temperature profile along thereaction pipe, including the pipe wall temperature, the process gas temperature, and the temperatureof the combustion gas used as energy for the process in the reformer furnace. The performanceevaluation of the reformer furnace uses a mathematical model for combustion in the furnace which canlater be developed by knowing the fitting composition of the conversion results. The type of reformerstudied is the top-fired reformer. The results of modeling using data from the steel industry obtained thehighest temperature from the combustion of gas from the burner which is in the reaction pipe at aposition 3-4 meters from the upper end of the reformer around 1300 oC and the temperature of naturalgas-steam in the pipe reaches 860 oC at the end of the pipe. reaction. The pipe wall heating with naturalo ogas fuels provides a maximum temperature ranging from 890 C - 895 C on the outer wall of thereaction pipe, and the pressure inside the reaction pipe ranges from 8.0-8.5 atm.